GREEN PRACTICES ON SUSTAINABILITY PERFORMANCE: THE MODERATING ROLE OF SLACK RESOURCES - Ramadana, Mariska; Julia, Julia; Wati, Erna (UI Scholars Hub, 2025)
Background: The growing urgency of environmental issues and economic imperatives has made sustainability a critical component of corporate strategy, particularly in developing countries like Indonesia. This study examines how green CEOs, green innovations, and green investments affect the sustainability performance of Indonesian companies listed in the Sri Kehati Index. Methods: Data from 2019 to 2023 were analyzed using regression analysis in STATA. The study also examined the moderating effect of absorbed and unabsorbed slack resources. Findings: The results show that a green CEO has no proven positive impact on sustainability performance, while green innovation has a negative impact. In contrast, green investment significantly improves sustainability performance. The results also show that slack resources do not significantly strengthen the relationship between green innovation and sustainability performance. Conclusion: This study emphasizes the importance of leadership committed to sustainability and strategic investment in improving firms' environmental performance. It also suggests that slack resources may be less effective in supporting the implementation of green innovation. Novelty/Originality of this article: This study highlights the impact of green investment on sustainability performance and its investigation of the moderating role of slack resources. By focusing on Indonesia, the study contributes novel insights to the existing literature on sustainability in emerging markets.